2021
DOI: 10.1002/jdd.12558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi‐professional education on the perceptions and awareness of oral health care among undergraduate nursing students in a nursing school

Abstract: This study investigates the effects of a study course in oral health care on the perceptions of nursing students. The course was designed and evaluated by a multi-professional team at a Japanese nursing school. Method:The subjects were 119 nursing students. They participated in the oral health course that comprised 45h of training in 4 years. These were designed and taught by oral health professionals, a certified speech-hearing therapist, and nurses. Questionnaires were distributed to subjects to compare thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Case-based learning of oral healthcare practice for patients in paediatric, cancer, perioperative, convalescent, psychiatric, and palliative care wards in hospitals was introduced in nursing oral healthcare courses. The learning might be effective in improving awareness [26,30]. In addition, the nursing students had participated in clinical training at various wards in some hospitals from the first to fourth years during the study period, and they might have observed nurses' oral healthcare practice there.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Case-based learning of oral healthcare practice for patients in paediatric, cancer, perioperative, convalescent, psychiatric, and palliative care wards in hospitals was introduced in nursing oral healthcare courses. The learning might be effective in improving awareness [26,30]. In addition, the nursing students had participated in clinical training at various wards in some hospitals from the first to fourth years during the study period, and they might have observed nurses' oral healthcare practice there.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on a previously developed questionnaire used to assess attitudes, awareness, and perceptions regarding oral healthcare among health professional students and healthcare workers [26,28].…”
Section: Structured Questionnairesmentioning
confidence: 99%
See 3 more Smart Citations